2003
DOI: 10.4040/jkan.2003.33.4.478
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Fatigue and Nutritional Status in Patients with Cancer Undergoing Radiotherapy

Abstract: The findings can be used by nurses who are taking care of patients undergoing radiotherapy. Considering the relationship between fatigue and nutritional status, nurses can identify the risk group most vulnerable to fatigue and malnourishment in order to provide appropriate interventions for them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Fatigue can occur as an acute or chronic state, most often observed in specific medical disorders such as cancer, heart failure, and stroke [30,31]. Impaired nutritional status has frequently been linked to fatigue in cancer patients [32,33]. Stobäus et al moreover showed that recent protein intake in cancer patients is associated with higher fatigue, implying that not only nutritional status but also acute dietary intake has an effect on fatigue [34].…”
Section: Discussionmentioning
confidence: 99%
“…Fatigue can occur as an acute or chronic state, most often observed in specific medical disorders such as cancer, heart failure, and stroke [30,31]. Impaired nutritional status has frequently been linked to fatigue in cancer patients [32,33]. Stobäus et al moreover showed that recent protein intake in cancer patients is associated with higher fatigue, implying that not only nutritional status but also acute dietary intake has an effect on fatigue [34].…”
Section: Discussionmentioning
confidence: 99%
“…This finding warrants additional investigation because the data on the relationship between BMI and fatigue are inconclusive 18,57,58…”
Section: Discussionmentioning
confidence: 99%
“…For example, in a study of 134 patients with breast cancer, women who received chemotherapy treatment reported greater fatigue severity than women receiving radiotherapy (Donovan et al 2004). Other studies have found that patients receiving both radiotherapy and chemotherapy treatment report higher fatigue scores than those receiving single modality treatment (Yang 2003, Bower et al 2006, Jereczek-Fossa et al 2007, indicating the probability of some association between treatment intensity and fatigue although the exact relationship is not clear.…”
Section: Treatment-related Factorsmentioning
confidence: 99%
“…When caloric intake is insufficient, the protein stored in muscles is broken down and used as an energy source. This type of malnutrition can lead to immune system compromise and possibly the development of fatigue (Yang 2003). Progressive weight loss with muscle wasting, called cachexia, is manifested clinically by fatigue (Brown 2002).…”
Section: Poor Nutritionmentioning
confidence: 99%